2006
DOI: 10.1590/s1020-49892006000400006
|View full text |Cite
|
Sign up to set email alerts
|

Fatores associados à vacinação contra a influenza em idosos

Abstract: The results suggest the need for campaigns to make information on the benefits of influenza vaccination more easily accessible to the elderly and health professionals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
1
48

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(70 citation statements)
references
References 27 publications
2
19
1
48
Order By: Relevance
“…The other ten studies analyzed vaccine coverage among the senior population. The majority of them were surveys conducted in representative samples of the target population, 7,9,13,16,17,20,24 and the remaining three among outpatients of a primary care clinic and reference hospitals 22,23,30 . Five surveys detected vaccine coverage similar to the Ministry of Health's (MOH) administrative data 9,13,16,17,30 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The other ten studies analyzed vaccine coverage among the senior population. The majority of them were surveys conducted in representative samples of the target population, 7,9,13,16,17,20,24 and the remaining three among outpatients of a primary care clinic and reference hospitals 22,23,30 . Five surveys detected vaccine coverage similar to the Ministry of Health's (MOH) administrative data 9,13,16,17,30 .…”
Section: Resultsmentioning
confidence: 99%
“…The majority of them were surveys conducted in representative samples of the target population, 7,9,13,16,17,20,24 and the remaining three among outpatients of a primary care clinic and reference hospitals 22,23,30 . Five surveys detected vaccine coverage similar to the Ministry of Health's (MOH) administrative data 9,13,16,17,30 . On the other hand, large differences were observed by the other three: among the elderly of two low income communities ("favelas") in the city of Rio de Janeiro, survey coverage was 50.2% and 38.3%, compared to MOH 75.7% coverage for the whole city; 66.3% coverage in Belo Horizonte, the country's third largest city, compared to 85.5% according to MOH data; and 83.8% among outpatients of a primary care clinic in Botucatu, state of São Paulo, compared to 62.2% (MOH) 7,22,24 .…”
Section: Resultsmentioning
confidence: 99%
“…This lack of vaccine uptake has been studied by various Brazilian authors, who have identified the following factors: age 14,15,16 , schooling 15,16 , and comorbidities 14,15,16 . Non-compliance was explained by some myths related to post-vaccination adverse events and even lack of belief in the vaccine 17 .…”
Section: Introductionmentioning
confidence: 99%
“…However, females prevailed among the vaccinated, a distinct result was found for the Spanish population, in which males were 38% more likely to receive the vaccine against pandemic influenza (16) . Investigations carried out with elderly in two municipalities did not observe statistical association between gender and adherence to the seasonal influenza vaccine (17)(18) . Gender is a characteristic that also appears to be unrelated to the severity of infection and the risk of mortality by the pandemic A (H1N1) (19) .…”
Section: Discussionmentioning
confidence: 73%